2019
DOI: 10.1161/circulationaha.118.037425
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombus Removal for Acute Iliofemoral Deep Vein Thrombosis

Abstract: Background: The ATTRACT Trial previously reported that pharmacomechanical catheterdirected thrombolysis (PCDT) did not prevent the post-thrombotic syndrome (PTS) in patients with acute proximal deep vein thrombosis (DVT). In the current analysis, we examine the effect of PCDT in ATTRACT patients with iliofemoral DVT. Methods: Within a large multicenter randomized trial, 391 patients with acute DVT involving the iliac and/or common femoral veins were randomized to PCDT with anticoagulation versus anticoagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(175 citation statements)
references
References 44 publications
5
160
0
10
Order By: Relevance
“…This suggests that, as we have reported elsewhere, improvements in these outcomes with PCDT was confined to the iliofemoral DVT subgroup. (13) The CAVENT (Catheter-Directed Venous Thrombolysis in Acute Iliofemoral Vein Thrombosis) trial, which evaluated 209 patients, reported that catheter-directed thrombolysis reduced the risk of PTS at 2 and 5 years but did not report findings separately for patients with femoral-popliteal (required involvement "above mid-thigh level") and iliofemoral DVT. (14;15) Our analysis has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that, as we have reported elsewhere, improvements in these outcomes with PCDT was confined to the iliofemoral DVT subgroup. (13) The CAVENT (Catheter-Directed Venous Thrombolysis in Acute Iliofemoral Vein Thrombosis) trial, which evaluated 209 patients, reported that catheter-directed thrombolysis reduced the risk of PTS at 2 and 5 years but did not report findings separately for patients with femoral-popliteal (required involvement "above mid-thigh level") and iliofemoral DVT. (14;15) Our analysis has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…(5;6) The Villalta scale rates the severity, from 0 to 3, of five patient-reported symptoms (pain, cramps, heaviness, pruritus, paresthesia) and six clinician-observed signs (edema, skin induration, hyperpigmentation, venous ectasia, redness, pain during calf compression). Points for symptoms and signs are summed into a total score (range 0-33), and patients can be categorized as having no PTS (score 0-4), mild PTS (score 5-9), moderate PTS (score [10][11][12][13][14] or severe PTS (score >14, or presence of ulcer). Patients were also counted as having PTS if they had an unplanned endovascular procedure to treat severe venous symptoms more than 6 months after randomization, unless there was a Villalta <5 in the preceding 4 weeks.…”
Section: Follow-up and Outcomesmentioning
confidence: 99%
“…In the study cohort (patients with proximal DVT including also ilio-femoral DVT) the rate of PTS (assessed by the means of the Villalta score) was 46.7 % in the thrombolysis arm and 48.2 % in anticoagulation group (p = 0.56) with higher rate of the major bleedings in the patients treated by thrombolytic treatment (1.7 % vs 0.3 %; p = 0.049). New published data with further analyses of ATTRACT results, regarding the group of the patients with DVT limited to the ilio-femoral segment (52). In this subpopulation the local thrombolysis was associated with a reduced rate of moderate and severe PTS (Villalta > 9) occurrence after 24 months of follow up (thrombolysis: 18 % vs anticoagulation: 28 %; p = 0.021).…”
Section: Open Vein Concept -Local Thrombolysis In Proximal Dvt Treatmmentioning
confidence: 90%
“…A new publication from the ATTRACT study has now shed more light on the trial with an analysis of the subgroup with iliofemoral disease alone with 196 patients in the PCDT group and 195 patients in the control group (34). These analyses are acknowledged by the authors to be limited by a less substantial power to detect differences in outcome compared to the overall trial and a substantial loss of patients to follow-up.…”
Section: Recent Literature With Rct's and Experience From Big Series mentioning
confidence: 99%